ASSESSMENT IN THE MERDEKA CURRICULUM: HOW ARE THE TEACHERS' PERSPECTIVES ON IT? - Robby Shadri; Neni Hermita; Dini Deswarni; Ayu Purnamasari S; Leny Julia Lingga; Hadion Wijoyo (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Assessment is a step to measure students’ learning outcomes. This paper discusses the teachers’ perception and understanding of how to carry out assessments in the Merdeka Curriculum. This paper also uses a qualitative descriptive survey research method with four stages; preparation, data collection, data analysis, and conclusions. Data collection techniques are carried out through interviews. The samples of the research are teachers from Penggerak School throughout Riau Province with a total population of 23 teachers. The data obtained are analyzed using descriptive statistical techniques. The results indicate that the implementation of the assessment in the Merdeka Curriculum, which consisted of diagnostic, formative, and summative assessments, is conducted by the teacher after the learning process is completed. Students’ learning outcomes are obtained from their knowledge, attitudes, and skills during learning activities. The student’s learning outcomes are presented in a school report based on the Merdeka Curriculum school report application. Thus, the teachers overall understand and have conducted the assessments that are required in the Merdeka Curriculum.